2018
DOI: 10.3897/bdj.6.e24071
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of bees (Hymenoptera: Apoidea) from managed emergent wetlands in the lower Mississippi Alluvial Valley of Arkansas

Abstract: BackgroundHere we present the results from a two-year bee survey conducted on 18 managed emergent wetlands in the lower Mississippi Alluvial Valley of Arkansas, USA. Sample methods included pan traps, sweep netting and blue-vane traps. We document 83 bee species and morphospecies in 5 families and 31 genera, of which 37 species represent first published state records for Arkansas. The majority of species were opportunistic wetland species; only a small number were wetland-dependent species or species largely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…A total of 44 species from 15 genera and four families were collected during July and August in 2018. The number of species documented in the current study is half than that reported by [ 32 ] in managed emergent wetlands within the lower Mississippi Alluvial Valley of Arkansas, USA, and one quarter of number of species reported by [ 33 ] in the Arkansas River Valley. Most of the bees collected from the current study belong to Halictidae family (89%) which is similar to other findings in which pan traps were used for collecting pollinators in earlier studies [ 34 ] in Oregon and [ 35 ] in Texas.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…A total of 44 species from 15 genera and four families were collected during July and August in 2018. The number of species documented in the current study is half than that reported by [ 32 ] in managed emergent wetlands within the lower Mississippi Alluvial Valley of Arkansas, USA, and one quarter of number of species reported by [ 33 ] in the Arkansas River Valley. Most of the bees collected from the current study belong to Halictidae family (89%) which is similar to other findings in which pan traps were used for collecting pollinators in earlier studies [ 34 ] in Oregon and [ 35 ] in Texas.…”
Section: Discussioncontrasting
confidence: 51%
“…The most abundant species in the current study consisted of L. imitatum (42.2%), followed by Augochlorella aurata (8.3%), L. subviridatum (6.8%), Agapostemon texanus (6.4%) and L. birkmani (4.1%). Surprisingly, in the study by [ 32 ], there was no report of L. imitatum , L. subviridatum and L. birkmani though both of the studies were conducted in the same state in Arkansas in the same season (during months of July through August), but in a different landscape and ecosystem. In another study conducted in a nearby location, Lasioglossum spp.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of this study is the substantial spatial coverage of our surveys, which resulted in data covering a large geographic range, a rarity among pollinator diversity studies (but see Westphal et al ., 2008; Le Féon et al ., 2010; Carril et al ., 2018; Stephenson et al ., 2018), particularly studies on pollinators in the prairies or plains regions (Jamieson et al ., 2019). Combined with a high number of replicates, this geographic coverage has resulted in a large data set that enriches our understanding of broad spatial patterns in bee communities.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Southeastern US, some habitats or landcover types of western Mississippi, for example, may provide important resources for this species as many of the plant species listed by Robertson (1928) as visited by F. condignus are frequently present in or amid wetland habitats in western Mississippi (Gunn et al 1980). Florilegus condignus was also recently detected in Arkansas wetlands, across the Mississippi River from where collections were made in Mississippi (Stephenson et al 2018). The phenological findings included in this paper alongside the description of a gynandromorph of F. condignus in Mississippi add to the generally limited knowledge about this species.…”
Section: Discussionmentioning
confidence: 61%